Native American and indigenous studies association (NAISA) annual meetings - Salomon Tarquini, Celia Claudia (2015)
Fil: Salomon Tarquini, Celia Claudia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Pampa. Facultad de Ciencias Humanas. Instituto de Estudios Sociohistóricos; Argentina